1983
DOI: 10.1128/jb.153.1.520-526.1983
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan of Legionella pneumophila: apparent resistance to lysozyme hydrolysis correlates with a high degree of peptide cross-linking

Abstract: Peptidoglycan (PG) from Legionella pneumophila was composed of muramic acid, glucosamine, glutamic acid, alanine, and meso-diaminopimelic acid in a molar ratio of 0.8:0.8:1.1:1.7:1. Partially purified PG contained trypsin-insensitive proteins which were extracted by 1 N NaOH hydrolysis without apparent dissolution of the PG. Lysozyme hydrolysis of purified PG or cell walls caused an increase in reducing groups which correlated with roughly 70 to 100% digestion of disaccharides. However, there was no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
1
21
0
1
Order By: Relevance
“…Purification of PG-PC from SCVs was easily accomplished. Proteins associated with the PG were resistant to proteolysis by trypsin, protease VI, and proteinease K. These results were similar to the resistance properties of proteins associated with the PG of Legionella pneumophila (1,2). Chemical analysis of the PG-PC indicated that a KDOlike component present in phase I lipopolysaccharide (3a, 20) copurified with this fraction, thus suggesting that LPS and protein were associated with the PG.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Purification of PG-PC from SCVs was easily accomplished. Proteins associated with the PG were resistant to proteolysis by trypsin, protease VI, and proteinease K. These results were similar to the resistance properties of proteins associated with the PG of Legionella pneumophila (1,2). Chemical analysis of the PG-PC indicated that a KDOlike component present in phase I lipopolysaccharide (3a, 20) copurified with this fraction, thus suggesting that LPS and protein were associated with the PG.…”
supporting
confidence: 63%
“…Proteolytic enzyme treatments of PG-PC. Samples (0.4 mg) were incubated at 370C with 50 Fg of trypsin, protease VI, and proteinase K (E. Merck AG, Darmstadt, West Germany) as previously described (1,2).…”
Section: Methodsmentioning
confidence: 99%
“…The bacterial cells were harvested by centrifugation at 100,000 x g for 30 min, washed twice with distilled water and lyophilized . Two hundred mg of dried cells were suspended in 50 ml of 4% sodium dodecyl sulfate (SDS), boiled for 1 hr, and cooled at room temperature as described before (1). After centrifugation, the residue was washed three times with distilled water .…”
Section: Methodsmentioning
confidence: 99%
“…Certain foreign surface antigens that have been cloned from closely related donor species have been shown to localize to the E. coli cell surface (13); however, molecules from distantly related species, such as streptococcal M protein, are not surface localized in E. coli (5). It is therefore surprising that L. pneumophila surface antigens are properly sorted in E. coli, as these two species are phylogenetically distant, having only 1 to 3% DNA homology (3), and as they possess cell envelopes with distinctly different structures (1,16).…”
Section: Discussionmentioning
confidence: 99%